Pendeteksian Wajah Bermasker Berbasis Android Menggunakan Algoritma Convolutional Neural Network (CNN) - Hutauruk , Daniel Jhon Rosinton; Herlawati , Herlawati; Hendharsetiawan , Andy Achmad (Journal of Students‘ Research in Computer Science, 2022)
The masks are an effort that must be made in that is why spreading viruses covid-19 while doing suitable activities indoors and out of the room. In doing suitable activities indoors and out of space we should use a mask to reduce the spread of the virus and must abide by protocols covid-19 health must be implemented in various aspects of life. For that reason, a system that detects the use of a mask when you implement an activity whether to use a mask or not use masks. To perform work use masks can use algorithms convolutional neural networks assisted by graphic user interface (GUI) platform and using the internet of things. Input from algorithm convolutional neural network and using a platform of the internet of things. Input from algorithm convolutional neural network in the form of a picture consisting of 120 image data consisting of 60 image data not wearing masks and 60 image data wearing a mask. The result of this research can detect the mask 100 % according to input image data.